Development Of a Hybrid System for Greywater Treatment Using Biochar Filter with Integration of Water Hyacinth - Lennevey, Kinidi; Darren T.R., Hillaby; Shanti Faridah, Salleh; Josephine Lai, Chang Hui; Florianna Lendai, Michael Mulok (The Italian Association of Chemical Engineering, 2025)
Greywater pollution poses a significant threat to environmental and public health, particularly in rapidly urbanizing regions. In this context, hybrid treatment systems that combine nature-based solutions offer a sustainable and cost-effective approach for decentralized wastewater management. This study investigates the synergistic effectiveness of a two-stage greywater treatment system integrating phytoremediation using Eichhornia crassipes (Water Hyacinth) with biochar filtration derived from palm kernel shells. System performance was evaluated based on the removal of ammoniacal nitrogen (AN) and chemical oxygen demand (COD) using standard APHA methods. FTIR-ATR spectroscopy was employed to characterize functional group changes on the biochar surface before and after treatment. Results showed that the phytoremediation unit significantly reduced AN (80.8 %) and COD (75.8 %). Subsequent biochar filtration enhanced these outcomes, achieving final cumulative removals of 85.5 % for AN and 89.3 % for COD. The combined system outperformed either component alone, highlighting the synergistic interaction between plant uptake and biochar adsorption in pollutant removal. Effluent pH approached neutrality, and FTIR analysis indicated organic compound adsorption on the biochar surface. These findings support the application of integrated phytoremediation–biochar systems as effective, low-cost solutions for greywater treatment in developing urban areas.